2016
DOI: 10.2308/acch-51454
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Executive Pay Structure and the Transparency of Restatement Disclosures

Abstract: SYNOPSIS Restatement disclosures have evolved into two basic categories: reissuances (Big “R”) and revisions (little “r”). A reissuance restatement requires an 8-K filing, whereas a revision restatement can be disclosed in less transparent ways. The high-transparency of a reissuance restatement disclosure (8-K) results in a greater likelihood of negative effects on companies, executives, and auditors (e.g., Plumlee and Yohn 2008; Burks 2010). Determining whether an 8-K filing is required involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 57 publications
(77 reference statements)
5
27
0
Order By: Relevance
“…Second, our findings on the consequences of immaterial errors extend prior research on the determinants of materiality judgments (e.g., Keune and Johnstone 2009;Acito et al 2009;Tan and Young 2015;Hogan and Jonas 2016). Our evidence that immaterial errors predict future reporting unreliability suggests immaterial errors are a useful indicator of largely unobservable lower level control deficiencies (i.e., less severe than material weakness, which is disclosed).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Second, our findings on the consequences of immaterial errors extend prior research on the determinants of materiality judgments (e.g., Keune and Johnstone 2009;Acito et al 2009;Tan and Young 2015;Hogan and Jonas 2016). Our evidence that immaterial errors predict future reporting unreliability suggests immaterial errors are a useful indicator of largely unobservable lower level control deficiencies (i.e., less severe than material weakness, which is disclosed).…”
supporting
confidence: 81%
“…We also extend prior research, summarized in Figure 1 and Appendix 1, that focuses on determinants of management's materiality decisions (e.g., Keune and Johnstone 2009;Acito et al 2009), including classifications of error corrections as revisions versus restatements (e.g., Tan and Young 2015;Hogan and Jonas 2016). In contrast, our analysis takes as given the designation of an error as immaterial and evaluates the consequences of immaterial errors, comparing them to the consequences of restatements.…”
Section: Comparison Of Our Contribution With Prior Studiesmentioning
confidence: 78%
“…In contrast to these studies, according to Bao et al (2021), CEO pay ratio and restatements are positively linked, while CEO power strengthens and CEO ability weakens this relationship. Hogan and Jonas (2016) found that CEO and CFO equity proportion increases and difference in CEO and CFO pay structure decreases restatements. However, Ghafoor et al (2019) reported an insignificant relationship between CEO equity compensation and enforcement activities.…”
Section: Ceo/cfo Compensationmentioning
confidence: 97%
“…They concluded that contrary to the expectations, directors choose contracts according to their private information and these choices have an effect on stock prices. Hogan & Jonas (2016) examined the structure of compensation payment and transparency of financial statements restatement. The results illustrated that the growth in bonus paid to the managers in form of stocks reduces the transparency of disclosure quality.…”
Section: Transparency and Quality Of Financial Informationmentioning
confidence: 99%